2014
DOI: 10.3390/toxins6082379
|View full text |Cite
|
Sign up to set email alerts
|

Bioreactor Study Employing Bacteria with Enhanced Activity toward Cyanobacterial Toxins Microcystins

Abstract: An important aim of white (grey) biotechnology is bioremediation, where microbes are employed to remove unwanted chemicals. Microcystins (MCs) and other cyanobacterial toxins are not industrial or agricultural pollutants; however, their occurrence as a consequence of human activity and water reservoir eutrophication is regarded as anthropogenic. Microbial degradation of microcystins is suggested as an alternative to chemical and physical methods of their elimination. This paper describes a possible technique o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…As released MCs may be present in the hydrogen peroxidetreated water, the treated water should not be used for any critical purposes without testing of the MC concentration. The degradation of the released/residual MCs might be enhanced by the use of stronger oxidants such as ozone (Onstad et al 2007) or bioreactors employing MC-degrading bacteria (Dziga et al 2014). While both methods of assisted degradation are technologically feasible they may be considered too expensive for agricultural purposes.…”
Section: Use Of H 2 O 2 For Elimination Of Cyanobacteria and Mcsmentioning
confidence: 99%
“…As released MCs may be present in the hydrogen peroxidetreated water, the treated water should not be used for any critical purposes without testing of the MC concentration. The degradation of the released/residual MCs might be enhanced by the use of stronger oxidants such as ozone (Onstad et al 2007) or bioreactors employing MC-degrading bacteria (Dziga et al 2014). While both methods of assisted degradation are technologically feasible they may be considered too expensive for agricultural purposes.…”
Section: Use Of H 2 O 2 For Elimination Of Cyanobacteria and Mcsmentioning
confidence: 99%
“…Such an arrangement not only suppresses the growth of cyanobacteria or induces their death, but also enables a simultaneous, fast degradation of the MC released from the cells disrupted by the algicide. Recently, some new methods of biological MC degradation have been presented [14][15][16], however these proposals only offer ex situ treatment of contaminated water in bioreactors designed for MC removal from filtered water. Another approach is in situ bioremediation, which requires the production of an enzyme that is capable of MC degradation by well-established heterologous systems and the release of the enzyme into the environment.…”
Section: The Efficiency Of Mlra In Environmentally Relevant Conditionsmentioning
confidence: 99%
“…These changes to each microbial consortium were paralleled by a significant decline in MC degradation kinetics. Overall, this study highlights the importance of integrating environmental conditions into the design and operation of biofiltration systems for MC biodegradation.Previous studies have demonstrated the complete biodegradation of MC-LR within laboratory scale biofiltration systems following a preliminary lag phase of removal [14][15][16][17]. However, the toxin removal efficiency and extent of this lag phase can vary significantly with bacterial composition, nutrient concentration, and other environmental parameters that are associated with the source water.…”
mentioning
confidence: 99%
“…However, the toxin removal efficiency and extent of this lag phase can vary significantly with bacterial composition, nutrient concentration, and other environmental parameters that are associated with the source water. Efforts to evolve biofiltration from a passive process into a more standardized, controlled, and perhaps "engineered", biological treatment process for targeted removal of pollutants will require a better understanding of the physiology and genetics of MC-degrading bacteria [12][13][14][18][19][20].Significant efforts have been made to isolate and characterize the specific MC-degrading bacterial populations during algal bloom events in the source water and sediments, and from full scale biological treatment units in drinking water treatment facilities [7][8][9]17,[21][22][23][24]. However, these studies have not fully explored how these isolates function in mixed bacterial communities, nor the influences of mutualistic or antagonistic interactions on biodegradation kinetics.…”
mentioning
confidence: 99%
See 1 more Smart Citation